Prevalence of Obesity in Medical students and its correlation with cardiovascular risk factors: Emergency Alarm for Today? - Purohit, G.; Shah, T.; Harsoda, J.M. (Kathmandu University Medical Journal, 2017)
Background It is predicted that the prevalence of overweight and obesity will rise significantly by 2015 in young population. Problem of overweight and obesity has been recognized as public health problem worldwide due to the fact that it increases the risk of chronic diseases such as Cardiovascular Diseases (CVD), stroke, diabetes, sleep apnoea, osteoarthritis etc. Objective To assess the body mass index in medical students and its association with various cardiovascular risk factors like blood pressure, dietary habits, and family history of cardiovascular diseases. Method A university based cross-sectional analytical study was conducted in Department of Physiology, Smt. B.K. Shah Medical Institute & Research Center, Vadodara, Gujarat. Data was collected through convenient sampling technique by using self-administered questionnaire followed by anthropometric measurement. Body Mass Index (BMI) of 138 first year medical students was assessed. Systolic blood pressure, diastolic blood pressure, pulse pressure, mean blood pressure, pulse rate and arterial oxygen saturation were measured. Result Data was compiled in excel sheet, analyzed for percentage and proportion. Chi square and Pearson correlation test were also applied and alpha error was set at 5% level. In comparison to the students with normal BMI, students with BMI >25 kg/m2 (N=49) showed significantly high blood pressure indices. Dietary habits and family history of cardiovascular diseases were also noted. Highly significant association of high BMI was found with elevated blood pressure (X2=7.4042***, p<0.001) and presence of family history of cardiovascular diseases X2=9.8625***, p<0.001). BMI is negatively correlated with SpO2 (r= -0.0504, p<0.05) and pulse rate, while positively correlated with systolic blood pressure (r=0.2736) and diastolic blood pressure (r=0.0275). Conclusion In conclusion, majority (more than 35%) of medical students were overweight, high prevalence of cardiovascular risk factors like family history, elevated blood pressure and less SpO2.